Neuroprotection after Traumatic Brain Injury in Heat-Acclimated Mice Involves Induced Neurogenesis and Activation of Angiotensin Receptor Type 2 Signaling. Issue 8 (August 2014) - Umschweif, Gali; Shabashov, Dalia; Alexandrovich, Alexander G; Trembovler, Victoria; Horowitz, Michal; Shohami, Esther
Long-term exposure of mice to mild heat (34°C ± 1°C) confers neuroprotection against traumatic brain injury (TBI); however, the underling mechanisms are not fully understood. Heat acclimation (HA) increases hypothalamic angiotensin II receptor type 2 (AT2 ) expression and hypothalamic neurogenesis. Accumulating data suggest that activation of the brain AT2 receptor confers protection against several types of brain pathologies, including ischemia, a hallmark of the secondary injury occurring following TBI. As AT2 activates the same pro-survival pathways involved in HA-mediated neuroprotection (e.g., Akt phosphorylation, hypoxia-inducible factor 1α (HIF-1α), and brain-derived neurotrophic factor (BDNF)), we examined the role of AT2 in HA-mediated neuroprotection after TBI. Using an AT2 -specific antagonist PD123319, we found that the improvements in motor and cognitive recovery as well as reduced lesion volume and neurogenesis seen in HA mice were all diminished by AT2 inhibition, whereas no significant alternations were observed in control mice. We also found that nerve growth factor/tropomyosin-related kinase receptor A (TrkA), BDNF/TrkB, and HIF-1α pathways are upregulated by HA and inhibited on PD123319 administration, suggesting that these pathways play a role in AT2 signaling in HA mice. In conclusion, AT2 is involved in HA-mediated neuroprotection, and AT2 activation may be protective and should be considered a novel drug target in the treatment of TBI patients.